EL GENERO GAYENNA (ARANEAE: ANYPHAENIDAE) - Ramírez, M. J.; Kochalka, J. A. (Acta Entomológica Chilena, 2022)
The taxonomy of the genus Gayenna is discussed. The genus is redefined, studying the characters of its type species, Gayenna americana Nicolet. On this basis, Gayenna should probably be considered monotypic, but the remaining species are mantained in the genus until future revisions of other genera can be done. Females of Gayenna americana Nicolet are figured, males are described for the first time. The genus Mezenina Strand is placed as a júnior synonym of Gayenna. Mezenina dorsalis (Simón) is newly synonymized with Gayenna americana.